2011
DOI: 10.1111/j.1365-2982.2011.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octreotide on jejunal hypersensitivity triggered by Cryptosporidium parvum intestinal infection in an immunocompetent suckling rat model

Abstract: Data confirms the relevance of the present rat model to postinfectious IBS studies and prompt further investigation of somatostatin-dependent regulatory interactions in cryptosporidiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Newborn rats infected by Cp displayed jejunal hypersensitivity to jejunal distension 120 days post-infection which was associated with increase in activated mast cells. 88, 89 Treatment with octreotide, 10 days post-infection, normalized visceral hypersensitivity, immune cells numbers and changes in the structure of the enteric nervous system. 89 No changes in intestinal motility or permeability in the post-infection stage were reported in this model.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Newborn rats infected by Cp displayed jejunal hypersensitivity to jejunal distension 120 days post-infection which was associated with increase in activated mast cells. 88, 89 Treatment with octreotide, 10 days post-infection, normalized visceral hypersensitivity, immune cells numbers and changes in the structure of the enteric nervous system. 89 No changes in intestinal motility or permeability in the post-infection stage were reported in this model.…”
Section: Animal Modelsmentioning
confidence: 99%
“…29 Recently, an immunecompetent suckling rat model was established. 1,22 In these studies, C. parvum infections were able to induce digestive hypersensitivity (a key pathophysiological factor in functional digestive disorders, such as irritable bowel syndrome), and the intestinal hypersensitivity was closely associated with intestinally activated mast cell accumulation. To date, there are no reports of the role of mast cells during C. parvum infection in cattle.…”
mentioning
confidence: 99%
“…The severity of infection and the onset of jejunal hypersensition are different which indicated that they are isolate dependent. Besides, Bai et al [44] also confirmed this model's reliability and found that the agonist of somatostatin could prevent the development of jejunal hypersensitivity in cryptosporidiosis. Trichinella spiralis (T. spiralis) is also a commonly used parasite to establish the PI-IBS model.…”
Section: Parasite Infection Induced Animal Modelmentioning
confidence: 83%